Microglial activation and neuroinflammation in Alzheimer's disease: a critical examination of recent history - Streit, Wolfgang J. (Frontiers in Aging Neuroscience, 2010)
The neurofibrillary degeneration that occurs in Alzheimer’s disease (AD) is thought to be the result of a chronic and damaging neuroinflammatory response mediated by neurotoxic substances produced by activated microglial cells. This neuroinflammation hypothesis of AD pathogenesis has led to numerous clinical trials with anti-inflammatory drugs, none of which have shown clear benefits for slowing or preventing disease onset and progression. In this paper, I make the point that AD is not an inflammatory condition, and reconstruct the sequence of events during the 1980s and 1990s that I believe led to the development of this faulty theory.